An experimental study of airflow behaviour around a standard 2-man bobsleigh - Chowdhury, H.; Alam, F.; Arena, S.; Mustary, I. (Procedia Engineering, 2013)
This paper examines the aerodynamic behaviour of a standard 2-man bobsleigh. Wind tunnel experiments were undertaken on a 50% scale model of 2-man bobsleigh. Wool tufts and smoke were used to visualise the airflow characteristics around the bobsleigh. It was found that the air enters into the bobsleigh cavity through multiple paths. The results suggest that the optimisation of the bumpers, particularly the rear bumpers, is not significantly effective for reducing the aerodynamic drag. Hence, better aerodynamic performance can be achieved by altering the size and shape of the nose as well as the sidewall curvature